The Finnish School on the Move programme: policy-making and implementation strategies for Italy - Antonio Borgogni (Pensa MultiMedia, 2018)
The aim of the article is to analyse from scientificand policy viewpoints the Finnish Schools on the Move program inferring strategies and actions applicable to the Italian case. The article presents, through a fact sheet, the actual Finnish situation about physical activity policies and research. The analysis of the updated scientific literature about the results is complemented by the description of the program's background and current design. From scientific point of view the article, beyond the literature review, is based on a documentary analysis on interviews (n=2) with key informants and field observations (n=3) of schools participating in the program. Presuming that there are not comprehensive models that can be transferred from a country to another, the article emphasizes, for the Italian case, the actions feasible at short term, changing rules at school level, those achievable at medium term, changing organization at community level, and those requiring deeper cultural and legislative modifications. At policy making level, it is plausible that some programs and actions of the Finnish program would be costless in Italy: some depend on a better destination of already available resources, several are possible through inter-sectors policies; all the strategies and actions, however, require to be assessed and monitored through researches entrusted to a university network in collaboration with sport and public health institutions and organizations.